Współczesna dyplomacja humanitarna – czy jest w niej miejsce dla organizacji pozarządowych? Studium przypadku Ukrainy - Małgorzata Myl-Chojnacka (Acta Iuris Stetinensis)
The paper aimed at presenting an evolution of a “humanitarian diplomacy” concept and at identifying factors that affect the process. It was also attempted to investigate a capacity of non-governmental organizations (NGOs) in field of the humanitarian diplomacy. The research was conducted using the historical and dogmatic methods. Theoretical considerations were complemented by practical analyzes of activities undertaken by NGOs in response to Russian invasion in Ukraine. The study showed that the humanitarian diplomacy is a heterogenic phenomenon and its understanding is influenced by priorities and targets that are established, as well as by actors that are involved in activities. However, it may be assumed that the humanitarian diplomacy consist in promoting different interactions aimed at providing peace, justice and help to affected communities. Importantly, these activities may be conducted not only by States, international organizations (eg. the United Nations) or specialized bodies (eg. International Committee of the Red Cross), but also by non-governmental organizations. The Ukrainian case revealed that in the field of humanitarian diplomacy NGOs present a huge potential that cannot be limited only to providing humanitarian support. Non-governmental organizations can also actively negotiate and advocate, thus strengthening capacity of achieving the gools of humanitarian diplomacy.